Analisis Tingkat Kecacatan Produk Cetak Kemasan Karton Lipat Dengan Pendekatan DMAIC Six Sigma - Saeful Imam; Wiwi Prastiwinarti (Politeknik Negeri Jakarta, 2020)
The map of competition in the business world in the industrial sector makes consumers' demands on the quality of products produced even higher so that the industry has an obligation to provide the best service to consumers in order to maintain the sustainability of its business. This is evenly distributed in all industrial sectors including the printing industry. Based on preliminary observations at one of the large printing presses in Jabodetabek the failure rate of printed folding carton packaging products produced is still quite large. The integrated production process makes the process results affect each other the number of defects in the next process. The results of observations show that of the 3 main processes of folding cardboard packaging production at PT.X, the aim of printing and ponding has the highest defect percentage of 47% and 44% of the total defect, while the glueing process has the lowest percentage of 7% with a total total defect of 827,347 packages of a total production of 4,735,350. From the results of data recapitulation and calculation of the number of defects, it can be seen that the sigma value of the company with the sample production data taken has an average sigma of 3.6. Through the application of the Six Sigma DMAIC method this research seeks to provide solutions in overcoming the problems of defective products that occur during the production process so that the main purpose of the printing industri in increasing productivity can be achieved.